A rare case of giant mucinous cystadenocarcinoma of the right ovary with metastatic deposits and Brenner tumor in the left ovary (Indian Journal of Case Reports, 2024)
Ovarian cancer is the second most common gynecological malignancy. Mucinous tumor accounts for 3% of ovarian tumors and is a challenging task for a surgical pathologist. Association of Brenner tumor, a subtype of epithelial malignancy is a rare entity reported in the literature. Herein, we report a unique case of a 57-years old post-menopausal woman who presented with progressive abdominal distention for 3 years and constipation for 1 year. Clinically, it was suspected as a case of complex ovarian cyst and the patient underwent staging laparotomy. Intraoperatively, a giant mucinous cystadenocarcinoma of the right ovary with deposits in the pouch of Douglas, omentum, umbilical, and the sub-umbilical region was found along with a benign Brenner tumor of the left ovary.